Identifikasi Jenis Gulma pada Areal Pertanaman Kelapa (Cocos nucifera L.) di Negeri Suli, Kecamatan Salahutu, Kabupaten Maluku Tengah - Joelens Klif Touwe; Wilma Laurien Tanasale; Abdul K Kilkoda (JURNAL PERTANIAN KEPULAUAN, 2022)
Coconut is one of the plantation crops that has experienced a decrease in production in the village of Suli, Central Maluku Regency. One of the causes of the reduction of coconut production in each planting area in Suli Village, Central Maluku Regency, is weeds. The drastic decline in coconut production from year to year in Suli village is due to weeds, so it is necessary to know the dominant weed species in the coconut plantation area in Suli village, Central Maluku Regency. The hypothesis put forward in this study is that weeds are prevalent in the coconut planting area. This study uses the "vegetation survey" method to collect data with field observations. In carrying out the vegetation analysis, the quadratic form was used with a sample plot measuring 1 m x 1 m on six coconut trees. For each coconut tree, three weed samples were taken under the coconut canopy, so a total of 18 weed samples were taken from under the coconut canopy. Qualitative and quantitative data were taken. The data needed in this study consists of primary data and secondary data. The dominant weed in the coconut plantation area in Suli Village, Central Maluku Regency, is the broadleaf weed Melastoma malabathricum L.